Cardiac autonomic responses induced by auditory stimulation with music is influenced by affinity - Plassa, Bruna O.; Milan, Réveni; Guida, Heraldo Lorena [UNESP]; Abreu, Luiz Carlos de; Raimundo, Rodrigo Daminello; Gonzaga, Luana A. [UNESP]; Valenti, Vitor Engrácia [UNESP] (GN1 Sistemas e Publicacoes, 2014)
INTRODUCTION: We aimed to evaluate the effects of musical auditory stimulation on cardiac autonomic regulation in subjects who enjoy and who do not enjoy the music. METHOD: The study was performed in young women (18-27 years old) divided in two groups (1) volunteers who enjoyed the music and (2) volunteers who did not enjoy the music. Linear indices of heart rate variability were analyzed in the time domain. The subjects were exposed to a musical piece (Pachelbel: Canon in D Major) during 10 minutes. Heart rate variability was analyzed at rest with no music and during musical auditory stimulation. RESULTS: In the group that enjoyed the music the standard deviation of normal-to-normal R-R intervals (SDNN) was significantly reduced during exposure to musical auditory stimulation. We found no significant changes for the other linear indices. The group composed of women who did not enjoy the music did not present significant cardiac autonomic responses during exposure to musical auditory stimulation. CONCLUSION: Women who enjoyed the music presented a significant cardiac autonomic response consisting of a reduction in heart rate variability induced by the musical auditory stimulation. Those who did not enjoy the musical piece presented no such response.

INTRODUÇÃO: O objetivo foi avaliar os efeitos da estimulação auditiva musical sobre a regulação autonômica cardíaca em indivíduos que gostam ou que não gostam da peça musical utilizada. MÉTODO: O estudo foi realizado em mulheres jovens (18-27 anos) divididas em dois grupos (1) voluntárias que gostavam da peça musical e, (2) voluntárias que não gostavam da peça musical. Índices lineares da variabilidade da frequência cardíaca foram analisados no domínio do tempo. Os indivíduos foram expostos a uma peça musical (Pachelbel: Canon in D major) durante 10 minutos. A variabilidade da frequência cardíaca foi analisada em repouso sem música e durante a estimulação auditiva musical. RESULTADOS: No grupo que gostava da peça musical o desvio-padrão dos intervalos RR normais-a-normal (SDNN) foi significativamente reduzido durante a exposição à estimulação auditiva musical. Não foram encontradas alterações significativas para os outros índices lineares. O grupo composto por mulheres que não gostavam da música não apresentou respostas autonômicas cardíacas significativas durante a exposição à estimulação auditiva musical. CONCLUSÃO: As mulheres que desfrutaram da música apresentaram resposta autonômica cardíaca significativa constituída por uma redução na variabilidade da frequência cardíaca induzida pela estimulação auditiva musical. Aqueles que não apreciavam a peça musical não apresentaram qualquer resposta autonômica.